KOMUNIKASI POLITIK DALAM REFORMASI PENDIDIKAN SEKOLAH DASAR: SEBUAH TINJAUAN LITERATUR - Zumiraj, Muhammad Alam; Gifari, Haikal; Harmonis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Educational reform is a crucial agenda in the effort to improve human resources quality in Indonesia. Political communication plays a central role in this process, particularly in the context of elementary education. This study employs a qualitative method with a literature review design to analyze relevant literature on political communication in the elementary education reform in Indonesia. The results indicate that effective political communication is essential for disseminating educational policies, garnering support, and overcoming resistance from various stakeholders. The main challenges include a lack of clarity in conveying information, low community participation, and insufficient feedback mechanisms. Successful communication strategies include the use of mass media and social media, participatory approaches, and training for stakeholders. Best practices from countries like Finland and Singapore highlight the importance of transparency and community participation in the educational reform process. Based on these findings, it is recommended that the government enhance the transparency and consistency of communication, encourage active community participation, develop effective feedback mechanisms, adopt international best practices, and improve stakeholders' communication skills. Thus, it is hoped that political communication in elementary education reform in Indonesia can be more effective and achieve the desired educational goals.   Keywords: educational reform, elementary school, political communication